KARAKTERISTIK PETANI DAN USAHATANINYA SERTA PENGARUHNYA TERHADAP PODUKTIVITAS PADI DI JAWA BARAT - Elly Rasmikayati; Sri Fatimah; Bobby Rachmat Saefudin (Fakultas Pertanian, Universitas Janabadra, 2024)
Rice is the main food commodity in Indonesia. The level of rice consumption in Indonesia reached 35.3 million tonnes. Based on these facts, rice production in Indonesia must be able to meet domestic consumption needs. However, now that Indonesia is experiencing a trend of decreasing rice harvested area, West Java, which is one of the provinces with the largest rice production in Indonesia, has not escaped the trend of decreasing rice harvested area. So it is necessary to increase rice productivity in this province. Therefore, the aim of this research is to examine the influence of the characteristics of farmers and their farming on rice productivity in West Java. This research uses quantitative methods with regression analysis methods as a data analysis tool. The number of respondents in this study was 281 rice farmers. This research shows that the majority of farmers in West Java are men aged 40-60 years with elementary school education and long farming experience. The majority of rice farmers in West Java incur seed costs of around IDR 100-200 thousand per hectare per season, with land rental costs under IDR 10 million per hectare per season, medicine costs range from IDR 1-5 million per hectare per season for the majority of farmers, labor costs are less than IDR 5 million per season. The results of the regression analysis reveal that partially the cost of fertilizer and tractor rental significantly affects rice productivity. Simultaneously, the variable factors in this research show a significant influence on rice productivity in West Java. Furthermore, the regression model formed can be used to predict rice productivity in West Java. Key-words: farmer characteristics; rice farming; linear regression; rice productivity;